PMI e responsabilità sociale: un’analisi empirica nel contesto italiano - Balluchi, Federica; Furlotti, Katia; Petruzziello, Anna (Piccola Impresa / Small Business, 2011)
Corporate Social Responsibility (CSR) has received growing attention over the last few years; it represents a voluntary approach taken by an enterprise to meet stakeholders’ expectations, considering their different features. In an increasingly turbulent environment and independent of size, activity and sector, companies cannot neglect to assume a solid social orientation while striving towards good economic and financial performance. As seen in the latest national and international studies, Small and Medium Enterprises (SMEs) worldwide have begun to show a strong sensitivity towards CSR. The very nature of SMEs does, indeed, by and of itself, imply a clear “socially-oriented” dimension; SMEs are deeply rooted in the local communities and many entrepreneurs instinctively understand that behaving correctly towards their employees, suppliers, the community and the surrounding environment represents a strong competitive factor. Unfortunately, this frequently fails to translate into careful planning and structuring of their socially-oriented activities, and into an adequate accountability process. In this sense, they need to formalize and add extra value to the CSR choices and to all the behaviours and strategies that would qualify the company to this end. In the light of this, it is the purpose of this paper to investigate the degree of awareness, attention and sensitivity that a sample of Italian SMEs (n. 509 associated to ConfartigianatoApla Parma) pays towards the varied facets of social responsibility. Specifically, the survey will be conducted by questionnaire with special attention to different types of stakeholders (employees, customers and suppliers, community, Institutions and environment). This will enable us to discuss the implications for dealing with stakeholders. From a methodological point of view, the research is divided into three main steps: 1. theoretical and empirical framework on the topic: SMEs and CSR; 2. empirical research: method; recording of data; analysis and interpretation of data; 3. conclusions, limits and further discussions.